PENGARUH INSENTIF DAN KOMPETENSI TERHADAP KINERJA GURU DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA SEKOLAH MENENGAH PERTAMA (SMP) DI KECAMATAN GROGOL KOTA CILEGON - Ahmad Halabi; Furtasan Ali Yusuf; Herawan Hayadi; Fatari Fatari (Yayasan Education and Social Center, 2026)
This study aims to determine the effect of incentives and competence on teacher performance with work motivation as an intervening variable in Junior High Schools in Grogol District, Cilegon City. The research method used is descriptive-quantitative research. This research method is an associative type of research. The population and sample size are 106. The results of this study are that incentives have a significant effect on performance of 69.3% (path coefficient 0.541). Competence has a significant effect on performance of 50.3% (path coefficient 0.202). Incentives have a significant effect on work motivation of 38.2% (path coefficient 0.243). Competence has a significant effect on work motivation of 44.3% (path coefficient 0.345). Work motivation has a significant effect on performance of 48.2% (path coefficient 0.187). Incentives do not significantly influence teacher performance through work motivation (path coefficient 0.045). Competence does not significantly influence teacher performance through work motivation (path coefficient 0.081). In conclusion, incentives and competence significantly influence teacher performance, incentives significantly influence work motivation, and work motivation significantly influences teacher performance. However, incentives and competence do not significantly influence teacher performance through work motivation as an intervening variable in junior high schools in Grogol District, Cilegon City.